Influência da sazonalidade climática e da seca prolongada sobre a qualidade das águas subterrâneas do Perímetro Irrigado do Baixo Acaraú - CE - Carvalho, Leonaria Luna Silva (2017)
The quality characteristics of water sources vary in space and time, and there is a need for monitoring. Thus, the objective was to identify the influence of climatic seasonality and prolonged drought on the groundwater quality in the Irido Perara Irado do Baixo Acaraú - CE. A participatory research was carried out with the lot owners to characterize these. We selected 37 points (wells, cacimbas and tanks) for hydrochemical analysis in June/2015, November/2015, June/2016 and November/2016. In the study to evaluate the prolonged drought were selected 6 points of the studied for comparison with data of November / 2010 and June/2011. The cluster analysis, using the agglomerative hierarchical method, was used using square Euclidean distance. The groups formed by the cluster analysis had averages compared by the T test at the level of p<0.05, by the SPSS 16.0 program. The characterization and the evaluation of the waters were done by the Piper diagram, in the waters for irrigation the methodology of the Laboratory of Salinity of the United States was used with the aid of the software QUALIGRAF 1.17 and the determination of the degree of restriction for use in the irrigation by the methodology of University Of California of Consultants. There was an increase in the demand for groundwater use due to the prolonged drought (2012 to 2016), mainly in the years 2014 and 2015, with more than 80% of the sources being used due to the drought. There is a lack of precise information and technical guidance on water quality. About 30% of producers have detected problems caused by groundwater quality. For the two-year study (2015 and 2016) it was verified that climatic seasonality did not influence water quality. Two groups were formed, in which group 2 (29% of the total samples) presented high levels of cations, mainly sodium, and chloride, presenting restrictions for human consumption and irrigation. In the hydrochemical classification there was a predominance of the sodium-chlorinated class, confirming the high presence of these ions in the analyzed waters. Regarding the classification of waters for irrigation for the groups, there was a predominance of C2S1 and C3S1 classes, with a higher salinity risk than sodicity. The dynamics of the water table indicated that the prolonged drought reduced the level of the water slide in the cacimbas. There were 2 groups. In group 2, the variables increased according to their location. In order to classify the irrigation water, there was not a greater influence of the drought in general, but for C8 there was, due to the location of this point. To classify irrigation water, there was a variation of classes C1S1 to C3S2.